2021
DOI: 10.1002/pd.6062
|View full text |Cite
|
Sign up to set email alerts
|

Conus medullaris migration during the third trimester: A retrospective study

Abstract: Objective To explore the migration process of the conus medullaris (CM) and propose a normal range of CM levels during the third trimester. Method We retrospectively collected the ultrasonographic and clinical data of 588 fetuses during the third trimester. We located the CM and assigned scores. One‐way analysis of variance and linear regression analyses were used to statistically analyze CM migration. Statistical significance was set at p < 0.05. Results The CM levels were statistically different among the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our previous studies have confirmed that both ultrasonography and MRI can be used to identify the fetal conus medullaris. 19,20 Meningocele and myelomeningocele belong to open dysraphic abnormalities, which is a prominent characteristic distinguishable from other diseases. Sacrococcygeal teratomas show conspicuous cystic or solid masses outside the spinal canal or inside the pelvis and abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have confirmed that both ultrasonography and MRI can be used to identify the fetal conus medullaris. 19,20 Meningocele and myelomeningocele belong to open dysraphic abnormalities, which is a prominent characteristic distinguishable from other diseases. Sacrococcygeal teratomas show conspicuous cystic or solid masses outside the spinal canal or inside the pelvis and abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving 588 fetuses during the third trimester, Sun et al suggested that a CM level at L3 vertebra in the third trimester can be a physiological condition but should be followed. The authors also reported that a fetus with a CM level above L1/2 intervertebral disc can have caudal regression syndrome 9 . In an anatomical dissection study with postmortem 30 fetuses, spinal cord length and CM level were found to be associated with the gestational age of the fetuses.…”
Section: Introductionmentioning
confidence: 94%